(untitled) (The International Journal for Scientific Research, 2024)
This study aimed to identify the impact of applying Total Quality Management in public utilities departments in the Kingdom of Saudi Arabia and to study the impact of its application on productivity. The study adopted the descriptive analytical approach, and the study community consisted of a number of workers in public utilities departments in government sectors. To achieve the study objectives, the study tool (questionnaire) was used as the main tool for collecting data, as it included (25) statements, and was distributed to (62) employees. (2) questionnaires were excluded, and after reviewing them, (60) questionnaires were found to be valid for analysis. The data were analyzed and hypotheses were tested using the Statistical Package for the Social Sciences (SPSS) program. The study showed several results, the most prominent of which are: The level of application of Total Quality Management in public utilities departments in the Kingdom of Saudi Arabia is medium to high, and there is also an impact of applying Total Quality Management in public utilities departments in the Kingdom of Saudi Arabia on the services provided and productivity. The study concluded with several recommendations, including that attention should be paid to training workers on modern methods of implementing tasks, as well as Attention must be paid to preparing the work environment in the organization to help employees be creative, in addition to paying attention to creating a research plan to identify beneficiaries’ expectations of a specific service.